Calculated Tumor Volume Is an Independent Predictor of Biochemical Recurrence in Patients Who Underwent Retropubic Radical Prostatectomy. (13th May 2012) - Tanaka, Nobumichi; Fujimoto, Kiyohide; Hirayama, Akihide; Nakai, Yasushi; Chihara, Yoshitomo; Anai, Satoshi; Tomioka, Atsushi; Shimada, Keiji; Konishi, Noboru; Hirao, Yoshihiko
Abstract : Purpose . The purpose of this study is to investigate whether the clinicopathological biopsy findings can predict the oncological outcome in patients who undergo radical prostatectomy. Materials and Methods . Between January 1997 and March 2006, 255 patients with clinically localized adenocarcinoma of the prostate (clinical T1-3N0M0) who had undergone retropubic radical prostatectomy were enrolled in this study. None of the patients received neoadjuvant or adjuvant therapy. Clinicopathological parameters were assessed to determine a predictive parameter of biochemical recurrence. Results . Of the total 255 patients, 77 showed biochemical recurrence during the follow-up period. The estimated 5-year overall survival, 5-year cause-specific survival, and 5-year biochemical recurrence-free survival rates were 97.7%, 99.5%, and 67.3%, respectively. Multivariate analysis using the Cox proportional hazards model showed that calculated cancer volume was an independent predictor among the preoperative clinicopathological parameters (P < 0.05 ). SVI and PSM were independent predictors among the postoperative parameters (SVI; P < 0.001, PSM; P = 0.049 ). Among the significant preoperative and postoperative parameters, calculated cancer volume remained an independent predictive parameter in multivariate analysis (P < 0.01 ). Conclusions . Tumor volume, as calculated by preoperative parameters, is an independent predictor of biochemical recurrence in patients who had undergone radical prostatectomy.